The Washback Effect in Online Language Assessment on Student's Learning Interest - Amalul Umam; Olivia Widad Zabidi (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2021)
This research was conducted with a descriptive-qualitative approach with a case study as the research design. Data was collected by conducting interviews via Google Form with open-ended questions, the number of students who were used as respondents was 30 students from the Department of English Education. This study aims to examine the assessment process in the summary of assignments for the Seminar Proposal course for the English Education Department. This rapidly growing world of technology also affects aspects of education, education can be run online without the need for face-to-face meetings. Especially at this time where the world is being hit by the Covid-19 virus which increasingly requires people to stay at home. Learning is done entirely at home by relying on online learning. Even so, teachers still need to pay attention to choosing the right assessment for students in order to produce a positive washback effect from each given task. The results of this study indicate that the assignment has a positive washback effect because it is considered capable of improving students' English skills and abilities.